Exploring relationships among stream health, human well-being, and demographics in Virginia, USA - Paul L. Angermeier (Elsevier, 2021)
Quantification of empirical relationships between ecosystem health and human well-being is uncommon at broad spatial scales. We used public data for Virginia (USA) counties to examine pairwise correlations among two indicators of stream health, thirteen indicators of human well-being, and four demographic metrics. Our indicators of stream health included the Virginia Stream Condition Index (VSCI) and the percentage of stream kilometers with a fish consumption advisory (%FCA); these measures are inversely related. VSCI and %FCA were correlated with some indicators of human health, safety and security, and living standards, as well as with some demographic metrics. VSCI was most strongly correlated (positively) with the percentage of a county’s population self-identifying as White; %FCA was most strongly correlated (positively) with overall mortality rate (number of deaths per 100,000 people). This exploratory study highlights the need for future multidisciplinary, multiscale studies to characterize toxicological, epidemiological, socioeconomic, and political linkages – including causal mechanisms – between ecosystem health and human well-being.